2015
DOI: 10.1212/nxi.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Early CNS neurodegeneration in radiologically isolated syndrome

Abstract: Objective:Increasing evidence indicates that the thalamus may be a location of early neurodegeneration in multiple sclerosis (MS). Our objective was to identify the presence of gray matter volume loss and thinning in patients with radiologically isolated syndrome (RIS).Methods:Sixty-three participants were included in this case-control study. Twenty-one patients with RIS were age- and sex-matched to 42 healthy controls in a 1:2 ratio. All participants underwent brain MRIs on a single 3T scanner. After lesion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 14 publications
10
133
4
1
Order By: Relevance
“…None of the patients admitted in the RIS phase, which is included in our study were receiving a conventional MS treatment. Most common complaint among the RIS patients was identified to be headache in various studies as found in this study (1,5,10).…”
Section: Resultssupporting
confidence: 52%
“…None of the patients admitted in the RIS phase, which is included in our study were receiving a conventional MS treatment. Most common complaint among the RIS patients was identified to be headache in various studies as found in this study (1,5,10).…”
Section: Resultssupporting
confidence: 52%
“…6,90,[104][105][106][107] Cross-sectional studies suggest that brain volume loss may be a better predictor of cognitive impairment than focal white matter lesion burden. 50,108 A recent investigation in patients with RIS reported cognitive impairment in 28% of patients and an association of higher T1 lesion volumes and lower cortical volumes with worse cognitive performance.…”
Section: Diffuse Gray Matter Damagementioning
confidence: 99%
“…112 Neuropathological and neuroimaging studies have revealed an extensive involvement of the thalamus and basal ganglia in patients with MS. Lesions in the deep gray matter nuclei frequently occur in MS, and thalamic atrophy is detectable in earliest disease stages which is easily assessable by measuring the third ventricle width on coronal T1-weighted MR images. 105,112 Interestingly, by means of a newly developed diffusion-weighted MRI tractography approach, reduced anatomical connectivity of the thalamus and the caudate nuclei was found in MS which was mainly located in areas spared by lesions. 113 A strong association of damage to strategically crucial deep gray matter nuclei such as thalamus or putamen with impaired cognitive processing has been demonstrated by multiple studies.…”
Section: Deep Gray Matter Damagementioning
confidence: 99%
“…Granberg et al [23] found that in half of the patients with RIS, headaches were the reason for MRI. In these patients, 2 out of 3 cases show a progression of MRI lesions over the next 2-5 years and in the same period one out of 3 cases fulfills the criteria for "classical" clinically isolated syndrome or MS. MRI investigations also show that the magnitude of the T2 lesions and signs of neurodegeneration do not differ between RIS patients and patients with early relapsing-remitting MS (RRMS, [24,25]). For interpretation of MRI findings, comparisons of the image morphology in MS and migraine sufferers could be helpful: Absinta et al [26] showed that in double inversion recovery imaging none of 32 migraine sufferers had cortical lesions, while they were found in 60% of patients with RRMS.…”
Section: Discussionmentioning
confidence: 99%